Targeting mucosal healing in Crohn's disease: what the clinician needs to know. (June 2019) - Klenske, Entcho; Bojarski, Christian; Waldner, Maximilian; Rath, Timo; Neurath, Markus F.; Atreya, Raja
In recent years, mucosal healing has emerged as a key therapeutic goal in the clinical management of patients with Crohn's disease, as it has been associated with improved long-term clinical outcomes. With the vast improvements in endoscopic imaging techniques and the increase in available treatment options, which reportedly are able to induce mucosal healing, the practising physician is left to wonder: how is endoscopic mucosal healing exactly defined in Crohn's disease, and how can it effectively be achieved and monitored in daily clinical practice? Within this review, we will give an overview of the ongoing debate about the definition of mucosal healing and the modalities to monitor inflammation, and finally present available therapies with the capacity to induce mucosal healing.